Candida and Oral Candidosis—A Review - Mallya, Sachidananda; Mallya, Shrikara (Journal of Health and Allied Sciences NU, 2019)
Oral candidiasis (also called candidosis) is an opportunistic infection affecting the oral mucosa. These lesions are very common and caused by yeast Candida albicans. C. albicans are normal component of oral microflora and around 30 to 50% carry these organisms. The rate of carriage increases with advancing age of the patient. C. albicans are recovered from patient’s mouth over the age of 60 years. Other species such as C. glabrata, C. tropicalis, C. guilliermondii, and C. krusei are infrequently but consistently isolated. Oral candidosis can be classified into primary and secondary candidiasis. The factors involved in the pathogenicity of C. albicans have been reviewed. The pathogenesis of different biotypes and strains of C. albicans varies. A relationship has been suggested between the adherence of C. albicans to surfaces and its ability to colonize and cause disease. An important aspect of the pathogenicity of C. albicans may be its nonspecific affinity and binding to acrylic resin and other plastics. The factors affecting adhesion of yeasts, related to yeast cells, related to host cells and environmental factors, and the main factors which increase the susceptibility of oral candidiasis have been reviewed. The different types of oral lesions, their identification by different methods, management, and treatment of oral candidiasis also have been highlighted.Oral candidosis as a common opportunistic infection has gained importance after the discovery of human immunodeficiency virus infection. Candidiasis was always an endogenous infection. There are few cases of exogenous infection in intravenous drug abusers and contact lens users. Esophageal candidiasis is the earliest and most cases of lesions seen in acquired immunodeficiency syndrome patient. The diagnosis and reporting of oral candidiasis should be done with utmost care. The finding of yeast cells in large numbers and presence of pseudohyphae indicate invasion and causative agent of infection. The diagnosis of Candida infection can be confirmed by various techniques and recently discovered advanced methods.The confirmation of Candida infection depends on clinical diagnosis, proper collection of specimen, and careful evaluation in methodology and reporting.
Keywords: Candida albicans; oral candidiasis; microflora